Waterproof coating and preparation method thereof
By using L-cysteine modified MoS2 and fluorosilane modified Zn and In modified CeO2 composite materials in waterproof coatings, combined with silane coupling agents, the problem of difficult to take into account both waterproofness and corrosion resistance in the prior art is solved, and the high water resistance and corrosion resistance of the coatings are achieved.
Patent Information
- Application Number
- CN202510046143.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The prior art is difficult to maintain excellent corrosion resistance while ensuring waterproofness.
The corrosion resistance of the coating is improved by adding L-cysteine modified MoS2 and fluorosilane modified Zn and In modified CeO2 composite materials to the waterproof coating, combined with silane coupling agent.
It significantly improves the water resistance and adhesion of waterproof coatings, while enhancing the corrosion resistance and mechanical properties of the coatings.
Smart Images

Figure BDA0005238469010000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of coatings, and more specifically, relates to a waterproof coating and a preparation method thereof. Background Art
[0002] Superhydrophobic materials are widely used in fields such as self-cleaning, oil-water separation, seawater desalination, anti-corrosion, antibacterial, anti-oxidation, and microfluidic transport. In the field of engineering, the corrosion of metal materials has always attracted much attention. In recent years, many corrosion protection studies have used the drainage of superhydrophobic surfaces to achieve anti-corrosion effects. Since metals will undergo chemical and electrochemical corrosion in the air, the metal surface needs to be treated into a superhydrophobic state to achieve a good anti-corrosion effect. Due to the rough structure of its concave and convex surface, the superhydrophobic surface forms a continuous and dense air film, which effectively prevents the corrosive medium from penetrating into the material base, which provides a new direction for corrosion protection research.
[0003] CN118027787A discloses a hydrophilic epoxy resin waterproof coating and its preparation method and application, the coating comprises an A component composed of an epoxy resin, a modified epoxy resin, a diluent and a coupling agent, and a B component composed of a curing agent, a modified curing agent and an accelerator, wherein the modified epoxy resin is prepared by mixing octadecyl methacrylate with bisphenol A epoxy resin. Compared with conventional epoxy resin waterproof coatings, the hydrophilic epoxy resin waterproof coating of the present invention has the following advantages: high permeability, more excellent waterproof performance, and simpler construction; good wetting performance, which can promote the adhesion between the coating and concrete, and can obtain better and longer waterproof effect; can be cured under low temperature and humid conditions; easy to flow, can achieve deep penetration into concrete under reasonable time conditions, no degumming, strong waterproof ability, and reasonable operation time, easy to construct; non-volatile, more green and environmentally friendly.
[0004] CN117925077A discloses an epoxy resin waterproof coating and its preparation method and application, the coating comprises an A component composed of modified bisphenol A epoxy resin, modified bisphenol F epoxy resin, a diluent and a coupling agent, and a B component composed of a curing agent, a modified curing agent and an accelerator, wherein the modified bisphenol A epoxy resin is prepared by modifying a bisphenol A type epoxy resin, and the modified bisphenol F epoxy resin is prepared by modifying a bisphenol F type epoxy resin. Compared with conventional concrete waterproof coatings, the epoxy resin waterproof coating of the present invention has the advantages of low viscosity, good curing effect under low temperature and humid conditions, high adhesion strength, high permeability, green environmental protection, etc. When used for concrete waterproofing, better waterproofing effect can be obtained, and no secondary pollution will be generated. At the same time, the coating can not only be firmly bonded to concrete, but also firmly bonded to other substrates, showing very good applicability, high use value, and good application prospects.
[0005] CN117186733A discloses a waterproof coating with anti-mildew performance and a preparation process thereof. In the preparation process of titanium-modified epoxy resin base material, the anti-mildew component with anti-bacterial and anti-mildew performance is first dispersed and adsorbed in the porous structure on the surface of nano titanium dioxide, and then gamma-aminopropyltriethoxysilane is grafted and adsorbed on the surface of nano titanium dioxide through coupling, so that the anti-mildew component dispersed in the porous structure on the surface of nano titanium dioxide can be locked and blocked to prevent the anti-mildew component from escaping from the porous structure on the surface of nano titanium dioxide; secondly, the group in gamma-aminopropyltriethoxysilane can react with the functional group in epoxy resin, so that nano titanium dioxide can be tightly combined between the molecular chains of epoxy resin, so that the epoxy resin has stable anti-bacterial and anti-mildew performance, and the water-resistant and waterproof performance of water-based coating is improved to a certain extent.
[0006] CN117025061A discloses a water-based epoxy waterproof coating and a preparation method thereof, wherein the water-based epoxy waterproof coating comprises component A and component B: the component A comprises the following components in parts by weight: 3 to 8 parts of anhydride curing agent, 1 to 5 parts of ethylene glycol dimethacrylate, 0.5 to 3 parts of polydimethylsiloxane, 5 to 10 parts of microcapsule-coated graphene, 1 to 3 parts of polyether-modified polysiloxane, 10 to 15 parts of deionized water, 1 to 3 parts of filler, 0.5 to 2 parts of red iron oxide, and 1 to 3 parts of 2-mercaptoethanol; the component B comprises the following components in parts by weight: 50 to 60 parts of water-based epoxy resin, 5 to 10 parts of polyethylene glycol diglycidyl ether, and 50 to 60 parts of deionized water; the mass ratio of the component A to the component B is 3:1. Through the above technical scheme, the problem of poor water resistance of the water-based epoxy waterproof coating in the prior art is solved.
[0007] It can be seen from the above content that although the above documents can achieve waterproofness, it is an urgent problem to be solved how to ensure waterproofness while still maintaining excellent corrosion resistance. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide a waterproof coating and a preparation method thereof. The raw materials of the anti-corrosion coating include: 80-100 parts of epoxy resin E44; 20-30 parts of L-cysteine-modified MoS2, 10-20 parts of fluorosilane-modified Zn and In-modified CeO2 composite materials; 10-20 parts of filler; 5-15 parts of auxiliary agent; 4-8 parts of curing agent; 30-40 parts of water. The waterproof coating of the present invention adds a silane coupling agent during the preparation process to significantly improve the waterproofness, and adds L-cysteine-modified MoS2 and modified cerium oxide, which together improve the corrosion resistance of the waterproof coating.
[0009] The purpose of the present invention is to provide a waterproof coating.
[0010] Another object of the present invention is to provide a method for preparing a waterproof coating.
[0011] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0012] A waterproof coating, wherein the raw materials of the anti-corrosion coating include the following components by weight: 80-100 parts of epoxy resin E44; 20-30 parts of L-cysteine-modified MoS2, 10-20 parts of fluorosilane-modified Zn and In-modified CeO2 composite materials; 10-20 parts of fillers; 5-15 parts of additives; 4-8 parts of curing agents; and 30-40 parts of water.
[0013] In the present invention, the preferred technical scheme is that the preparation method of L-cysteine-modified MoS2 comprises the following steps:
[0014] (1) ultrasonically dispersing molybdenum salt and thiourea in deionized water, then subjecting the mixture to a hydrothermal reaction, washing, and drying at a certain temperature to a constant weight to obtain MoS2;
[0015] (2) Add the MoS2 and L-cysteine prepared in step (1) to deionized water, and ultrasonically disperse for 20 to 40 minutes. Then, stir at 25 to 35° C. for 20 to 28 hours under an inert atmosphere, filter, wash, and vacuum dry at 70 to 90° C. for 10 to 14 hours to obtain L-cysteine-modified MoS2.
[0016] Preferably, in step (1), the hydrothermal reaction conditions are 180-200° C. for 16-24 h; the drying temperature is 70-100° C.; the molybdenum salt is at least one of sodium molybdate, potassium molybdate or ammonium molybdate; and the molar ratio of the molybdenum source to thiourea is 1:3.5-5.5.
[0017] Preferably, in step (2), the mass ratio of MoS2 to L-cysteine is 1:0.6 to 1.0.
[0018] In the present invention, the preferred technical solution is that the preparation method of the fluorosilane-modified Zn and In-modified CeO2 composite material comprises the following steps:
[0019] (a) adding zinc salt, indium salt and cerium salt to deionized water, ultrasonically dispersing for 20 to 30 minutes to obtain a mixed salt solution, then dropping an alkali solution with a concentration of 1 to 3 mol / L, adjusting the pH of the mixed salt solution to 10 to 12, standing for 3 to 5 hours, filtering, washing, drying at 80 to 100° C. for 10 to 20 hours, and calcining at 500 to 600° C. for 3 to 5 hours to obtain Zn and In modified CeO2;
[0020] (b) adding the Zn and In modified CeO2 and fluorosilane coupling agent obtained in step (a) to ethanol, stirring at 50-70° C. for 1-3 h; filtering, washing, and drying at 80-100° C. for 10-20 h to obtain a fluorosilane modified Zn and In modified CeO2 composite material.
[0021] Preferably, in step (a), the zinc salt is at least one of zinc nitrate, zinc chloride, and zinc acetate; the alkaline solution is a sodium hydroxide solution; the indium salt is at least one of indium nitrate, indium chloride, and indium acetate; the cerium salt is at least one of cerium nitrate, cerium chloride, and cerium acetate; and the molar ratio of the zinc salt, the indium salt, and the cerium salt is: 0.02-0.04:0.04-0.06:1.
[0022] Preferably, in step (b), the mass ratio of the product A to the fluorosilane coupling agent is 1:0.2-0.4; and the fluorosilane coupling agent is perfluorooctyltriethoxysilane.
[0023] In the present invention, the preferred technical solution is that the filler is nano titanium dioxide; and the curing agent is benzophenone tetraacid dianhydride.
[0024] In the present invention, the preferred technical solution is that the additives are dispersants, film additives, defoamers, silane coupling agents, leveling agents and anti-settling agents; further preferably, the dispersant is BYK163, the film additive is ethylene glycol butyl ether alkyd, the defoamer is BYK20, the leveling agent is diacetone alcohol; the anti-settling agent is polyethylene wax; the silane coupling agent is methyltrimethoxysilane;
[0025] A preparation method for a waterproof coating based on the above-mentioned method includes the following steps: first, epoxy resin; silane functionalized composite material; L-cysteine modified MoS2, fluorosilane modified Zn and In modified CeO2 composite material and water are put into a high-speed mixer and mixed at a stirring rate of 3000-5000 r / min for 20-40 minutes; then, fillers and additives are added to the above mixture and stirring is continued for 20-40 minutes; finally, a curing agent is added and stirring is continued for 10-30 minutes to obtain a waterproof coating.
[0026] The present invention has the following beneficial effects:
[0027] In the preparation process, the present invention improves the waterproof performance of the coating by adding the silane coupling agent methyltrimethoxysilane, and improves the corrosion resistance of the coating by adding MoS2 and modified CeO2. The L-cysteine-modified MoS2 and the fluorosilane-modified Zn and In-modified CeO2 composite materials promote the dispersion and bonding strength of MoS2 and modified CeO2 in the epoxy resin, thereby improving the corrosion resistance and the mechanical properties. DETAILED DESCRIPTION
[0028] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0029] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0030] The additives used in the embodiments and comparative examples of the present invention are dispersants, film additives, defoamers, silane coupling agents, leveling agents and anti-settling agents. Among them, the dispersant is BYK163, the film additive is ethylene glycol butyl ether alkyd, the defoamer is BYK20, the leveling agent is diacetone alcohol; the anti-settling agent is polyethylene wax; and the silane coupling agent is methyltrimethoxysilane. All of them can be purchased from the market; in the present invention, the dispersant, film additive, defoamer, silane coupling agent, leveling agent and anti-settling agent have the same quality.
[0031] The filler in the examples and comparative examples of the present invention is nano titanium dioxide; the curing agent is benzophenone tetraacid dianhydride.
[0032] Example 1
[0033] A waterproof coating, wherein the raw materials of the anti-corrosion coating include the following components by weight: 490 parts of epoxy resin E4; 25 parts of L-cysteine-modified MoS2, 15 parts of fluorosilane-modified Zn and In-modified CeO2 composite material; 15 parts of filler; 10 parts of auxiliary agent; 6 parts of curing agent; 35 parts of water;
[0034] The preparation method of the L-cysteine-modified MoS2 comprises the following steps:
[0035] (1) 1 mol of ammonium molybdate and 4.5 mol of thiourea were ultrasonically dispersed in 200 mL of deionized water, and then hydrothermally reacted at 190 °C for 20 h, washed, and dried at 90 °C to constant weight to obtain MoS2;
[0036] (2) 10 g of MoS2 prepared in step (1) and 8 g of L-cysteine were added to 150 mL of deionized water, and ultrasonically dispersed for 30 min. The mixture was then stirred at 30 ° C for 24 h under an inert atmosphere, filtered, washed, and vacuum dried at 80 ° C for 12 h to obtain L-cysteine-modified MoS2.
[0037] The preparation method of the fluorosilane-modified Zn and In-modified CeO2 composite material comprises the following steps:
[0038] (a) 0.03 mol zinc acetate, 0.05 mol indium chloride and 1 mol cerium acetate were added to 200 mL deionized water, and ultrasonically dispersed for 25 min to obtain a mixed salt solution, and then a 2 mol / L sodium hydroxide solution was added dropwise, and the pH of the mixed salt solution was adjusted to 11, and the mixture was allowed to stand for 4 h, filtered, washed, dried at 90 ° C for 16 h, and calcined at 550 ° C for 4 h to obtain Zn and In modified CeO2;
[0039] (b) Add 10 g of Zn and In modified CeO2 obtained in step (a) and 3 g of perfluorooctyltriethoxysilane to 150 mL of ethanol and stir at 60 °C for 2 h; filter, wash, and dry at 100 °C for 10 h to obtain a fluorosilane-modified Zn and In modified CeO2 composite material.
[0040] The preparation method of the waterproof coating comprises the following steps: firstly, epoxy resin; silane functionalized composite material; L-cysteine modified MoS2, fluorosilane modified Zn and In modified CeO2 composite material and water are put into a high-speed stirrer for mixing at a stirring rate of 4000r / min for 30 minutes; then fillers and additives are added to the above mixture and stirring is continued for 30 minutes; finally, a curing agent is added and stirring is continued for 20 minutes to obtain the waterproof coating.
[0041] Example 2
[0042] The difference between Example 2 and Example 1 is that: the raw materials of the anticorrosive coating include the following components by weight: 100 parts of epoxy resin E44; 20 parts of L-cysteine-modified MoS2, 20 parts of fluorosilane-modified Zn and In-modified CeO2 composite materials; 10 parts of filler; 15 parts of auxiliary agent; 4 parts of curing agent; 40 parts of water;
[0043] Example 3
[0044] The difference between Example 2 and Example 1 is that, in parts by weight, the raw materials of the anti-corrosion coating include the following components: 80 parts of epoxy resin E44; 30 parts of L-cysteine-modified MoS2, 10 parts of fluorosilane-modified Zn and In-modified CeO2 composite materials; 20 parts of filler; 5 parts of auxiliary agent; 8 parts of curing agent; and 30 parts of water.
[0045] Comparative Example 1
[0046] The difference between Comparative Example 1 and Example 1 is that MoS2 is not modified with L-cysteine.
[0047] Comparative Example 2
[0048] The difference between Comparative Example 2 and Example 1 is that the Zn and In modified CeO2 composite material is not modified by fluorosilane.
[0049] Comparative Example 3
[0050] The difference between Comparative Example 3 and Example 1 is that an equal amount of a fluorosilane-modified Zn-modified CeO2 composite material is used to replace the fluorosilane-modified Zn and In-modified CeO2 composite material.
[0051] The preparation method of the fluorosilane-modified Zn-modified CeO2 composite material comprises the following steps:
[0052] (a) 0.08 mol zinc acetate and 1 mol cerium acetate were added to 200 mL deionized water, and ultrasonically dispersed for 25 min to obtain a mixed salt solution, and then a 2 mol / L sodium hydroxide solution was added dropwise, and the pH of the mixed salt solution was adjusted to 11, and the mixture was allowed to stand for 4 h, filtered, washed, dried at 90 ° C for 16 h, and calcined at 550 ° C for 4 h to obtain Zn-modified CeO2;
[0053] (b) Add 10 g of Zn-modified CeO2 obtained in step (a) and 3 g of perfluorooctyltriethoxysilane to 150 mL of ethanol and stir at 60°C for 2 h; filter, wash, and dry at 100°C for 10 h to obtain a fluorosilane-modified Zn-modified CeO2 composite material.
[0054] Comparative Example 4
[0055] The difference between Comparative Example 4 and Example 1 is that L-cysteine-modified MoS2 is used to replace the fluorosilane-modified Zn and In-modified CeO2 composite material. 40 parts of L-cysteine-modified MoS2.
[0056] The waterproof performance of Examples 1-3 was tested, and the test results are shown in Table 1, where:
[0057] Waterproof performance: tested in accordance with GB / T1733-93.
[0058] Table 1:
[0059] Example 1 Example 2 Example 3 Water resistance / 30d No foaming No foaming No foaming
[0060] It can be seen from Table 1 that the waterproof coating prepared by the present invention has excellent water resistance.
[0061] The performance of the waterproof coatings of Examples 1-3 and Comparative Examples 1-4 was tested, and the specific results are shown in Table 2:
[0062] Adhesion (tensile adhesion): GB / T5210; anti-corrosion performance is tested according to national standards GB / T 9274-88 and GB / T1771-91.
[0063] Table 2
[0064]
[0065] It can be seen from Table 2 that the waterproof coating prepared by the present invention has excellent adhesion and corrosion resistance. In addition, by comparing the embodiment with the comparative example, it can be seen that the present invention promotes the dispersion and bonding strength of MoS2 and modified CeO2 in epoxy resin by using L-cysteine modified MoS2 and fluorosilane modified Zn and In modified CeO2 composite materials, improves corrosion resistance, and also improves mechanical properties.
[0066] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A waterproof coating, characterized in that: The raw materials of the anti-corrosion coating include the following components by weight: 80-100 parts of epoxy resin E44; 20-30 parts of L-cysteine-modified MoS2, 10-20 parts of fluorosilane-modified Zn and In-modified CeO2 composite materials; 10-20 parts of filler; 5-15 parts of auxiliary agent; 4-8 parts of curing agent; and 30-40 parts of water.
2. A waterproof coating according to claim 1, characterized in that: The preparation method of the L-cysteine-modified MoS2 comprises the following steps: (1) ultrasonically dispersing molybdenum salt and thiourea in deionized water, then subjecting the mixture to a hydrothermal reaction, washing, and drying at a certain temperature to a constant weight to obtain MoS2; (2) Add the MoS2 and L-cysteine prepared in step (1) to deionized water, and ultrasonically disperse for 20 to 40 minutes. Then, stir at 25 to 35° C. for 20 to 28 hours under an inert atmosphere, filter, wash, and vacuum dry at 70 to 90° C. for 10 to 14 hours to obtain L-cysteine-modified MoS2.
3. A waterproof coating according to claim 2, characterized in that: In step (1), the hydrothermal reaction conditions are 180-200° C. for 16-24 hours; the drying temperature is 70-100° C.; the molybdenum salt is at least one of sodium molybdate, potassium molybdate or ammonium molybdate; and the molar ratio of the molybdenum source to thiourea is 1:3.5-5.
5.
4. A waterproof coating according to claim 2, characterized in that: In step (2), the mass ratio of MoS2 to L-cysteine is 1:0.6-1.
0.
5. A waterproof coating according to claim 1, characterized in that: The preparation method of the fluorosilane-modified Zn and In-modified CeO2 composite material comprises the following steps: (a) adding zinc salt, indium salt and cerium salt to deionized water, ultrasonically dispersing for 20 to 30 minutes to obtain a mixed salt solution, then dropping an alkali solution with a concentration of 1 to 3 mol / L, adjusting the pH of the mixed salt solution to 10 to 12, standing for 3 to 5 hours, filtering, washing, drying at 80 to 100° C. for 10 to 20 hours, and calcining at 500 to 600° C. for 3 to 5 hours to obtain Zn and In modified CeO2; (b) adding the Zn and In modified CeO2 and fluorosilane coupling agent obtained in step (a) to ethanol, stirring at 50-70° C. for 1-3 h; filtering, washing, and drying at 80-100° C. for 10-20 h to obtain a fluorosilane modified Zn and In modified CeO2 composite material.
6. A waterproof coating according to claim 5, characterized in that: In step (a), the zinc salt is at least one of zinc nitrate, zinc chloride, and zinc acetate; the alkaline solution is a sodium hydroxide solution; the indium salt is at least one of indium nitrate, indium chloride, and indium acetate; the cerium salt is at least one of cerium nitrate, cerium chloride, and cerium acetate; and the molar ratio of the zinc salt, the indium salt, and the cerium salt is 0.02-0.04:0.04-0.06:
1.
7. A waterproof coating according to claim 5, characterized in that: In step (b), the mass ratio of the product A to the fluorosilane coupling agent is 1:0.2-0.4; the fluorosilane coupling agent is perfluorooctyltriethoxysilane.
8. A waterproof coating according to claim 1, characterized in that: The filler is nano titanium dioxide; the curing agent is benzophenone tetraacid dianhydride.
9. A waterproof coating according to claim 1, characterized in that: The auxiliary agents are dispersants, film auxiliary agents, defoaming agents, silane coupling agents, leveling agents and anti-settling agents.
10. A method for preparing a waterproof coating according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: firstly, epoxy resin, silane functionalized composite material, L-cysteine modified MoS2, fluorosilane modified Zn and In modified CeO2 composite material and water are put into a high-speed stirrer for mixing at a stirring rate of 3000-5000 r / min for 20-40 minutes, then fillers and additives are added to the mixture and stirring is continued for 20-40 minutes, and finally a curing agent is added and stirring is continued for 10-30 minutes to obtain a waterproof coating.
Citation Information
Patent Citations
Waterborne epoxy waterproof coating and preparation method thereof
CN117025061A
Waterproof coating with anti-mildew performance and preparation process thereof
CN117186733A
Epoxy resin waterproof coating as well as preparation method and application thereof
CN117925077A
Molybdenum disulfide corrosion-resistant coating and preparation method thereof
CN109233560A
Double-component anti-corrosion coating
CN112760008A
Cited By
Waterproof coating prepared based on waste down and preparation method thereof
CN120484696B